2021
DOI: 10.1002/ieam.4381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technological innovation and industrial‐structure upgrades on ecological efficiency in China in terms of spatial spillover and the threshold effect

Abstract: In the past 40 years, China's rapid industrialization has resulted in remarkable social progress and regional economic prosperity but also has caused problems, such as excessive resource consumption and environmental pollution. Ecological efficiency is an important indicator of whether economic efficiency and environmental efficiency are balanced. Exploring ecological efficiency is vital for achieving sustainable development, as technological innovation, industrial structure upgrading, and ecological efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The coefficient of industrial structure advancement is 0.098, which have passed the significance test, there is a positive correlation between industrial structure advancement and GTFP. This is consistent with Meng Huang's [42] research conclusions. The reason for this finding may be that the development of the economy mainly depends on resources and energy consumption because of abundant natural resources in the Yellow River Basin, forming many resource-dependent industries.…”
Section: Overall Analysissupporting
confidence: 91%
“…The coefficient of industrial structure advancement is 0.098, which have passed the significance test, there is a positive correlation between industrial structure advancement and GTFP. This is consistent with Meng Huang's [42] research conclusions. The reason for this finding may be that the development of the economy mainly depends on resources and energy consumption because of abundant natural resources in the Yellow River Basin, forming many resource-dependent industries.…”
Section: Overall Analysissupporting
confidence: 91%
“…Moreover, the driving force of smart cities in accelerating economic growth is enhanced steadily with the improvement of financial development and information sharing [ 25 ]. The influence of smart factors on the efficiency and quality of urban development has been furtherly analyzed [ 26 ], among which the urban innovation level, the degree of government intervention, financial development level [ 27 , 28 ], foreign trade [ 29 ], and urbanization have been demonstrated to be conducive to the green economic development, industrial structure [ 30 ], and modernization [ 31 , 32 ]. Additionally, telecommunication construction is supposed to break regional market restrictions and reduce the coordination cost of enterprises, which is crucial to facilitate integrated market construction and improve production efficiency through the scale and intensive economy [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…China's natural gas, electricity and other energy supply industries have 131 higher ecological efficiency than mining and other industries, The main reason for the 132 high eco-efficiency is that China's oil and gas exploration and production areas are 133 under state control . Scholars also found that the upgrading of 134 industrial structure and educational level generally have a positive impact on ecological 135 efficiency (Han et al, 2021;Huang et al, 2020;Wang et al, 2020;Yasmeen et al, 2020).…”
Section: Ecological Efficiency Estimationsmentioning
confidence: 99%
“…On the relationship between technological innovation and ecological efficiency, scholars' research results are inconsistent. Some scholars believe that technological innovation has a significant negative impact on ecological efficiency, but the interaction between technological innovation and industrial structure can improve regional ecological efficiency (Huang et al, 2020).…”
Section: Technological Innovation and Ecological Efficiencymentioning
confidence: 99%